2012
DOI: 10.3390/ijms131115321
|View full text |Cite
|
Sign up to set email alerts
|

Primary, Secondary Metabolites, Photosynthetic Capacity and Antioxidant Activity of the Malaysian Herb Kacip Fatimah (Labisia Pumila Benth) Exposed to Potassium Fertilization under Greenhouse Conditions

Abstract: A randomized complete block design was used to characterize the relationship between production of total phenolics, flavonoids, ascorbic acid, carbohydrate content, leaf gas exchange, phenylalanine ammonia-lyase (PAL), soluble protein, invertase and antioxidant enzyme activities (ascorbate peroxidase (APX), catalase (CAT) and superoxide dismutase (SOD) in Labisia pumila Benth var. alata under four levels of potassium fertilization experiments (0, 90, 180 and 270 kg K/ha) conducted for 12 weeks. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 92 publications
(88 reference statements)
8
57
0
4
Order By: Relevance
“…In this sense, Ibrahim et al [11] reported an increase of 1.22 to 1.82 mg GAE/g extract when applying 0 to 270 kg of K + /ha in Labisia pumila Benth, and also obtained similar results for …”
Section: Total Phenolic Compounds Flavonoids and Anthocyanins Contentsupporting
confidence: 62%
See 3 more Smart Citations
“…In this sense, Ibrahim et al [11] reported an increase of 1.22 to 1.82 mg GAE/g extract when applying 0 to 270 kg of K + /ha in Labisia pumila Benth, and also obtained similar results for …”
Section: Total Phenolic Compounds Flavonoids and Anthocyanins Contentsupporting
confidence: 62%
“…In this sense, Ibrahim et al [11] reported an increase of 1.22 to 1.82 mg GAE/g extract when applying 0 to 270 kg of K + /ha in Labisia pumila Benth, and also obtained similar results for flavonoids, reporting values from 0.68 to 0.94 mg g −1 of rutin in leaves of this plant by increasing K + . Flanigan and Niemeyer [13] found values from 13.1 to 26.9 mg GAE/g DW for ten basil cultivars.…”
Section: Total Phenolic Compounds Flavonoids and Anthocyanins Contentsupporting
confidence: 59%
See 2 more Smart Citations
“…12;2017 available for secondary biosynthetic routes. Whether it's true, then any environmental factor can trigger activation some pathway signal transduction lead to a response related to photosynthesis, growth and, consequently, primary metabolism could also affect the secondary metabolism (Ibrahim et al, 2012). Thus, occurrence of high night temperature can be considered one of these factors and in a future climate scenarios, the increase in global temperature as result of climate change could lead to changes in plant secondary metabolites biosynthesis altering the source-sink flow and consequently NSC accumulation and remobilization to grain filling; beyond plant capacity to respond to biotic and abiotic stresses could be altered.…”
Section: Discussmentioning
confidence: 99%